Словообразовательная симметрия двух симметричнвых смыслов в русском языке - Косова, Вера (Studia Rossica Posnaniensia, 2015)
This article analyzes word-formation categories that represent the beginning and end of an action in the modern Russian language, i.e. their semantic structure, motivational basis, means of expression as well as pragmatic and cognitive peculiarities. The conclusion is that these categories are asymmetrical in the Russian language and an attempt is made to explain the causes of this phenomenon.